Legal Protection of Well-Known Brands in Different Classes of Goods Case Study of Starbuck Corporation (Analysis of District Court Decision No: 51/Pdt.Sus/Merek/2021/PN Niaga Jkt.Pst Juncto Supreme Court Decision Number 836 K/Pdt.Sus-HKI/2022) - Suswandaru, Ari; Ahmed, Abdussalam Ali (Yayasan Sinergi Kawula Muda, 2023)
Mark is a part of Intellectual Property Rights (HKI) which functions as a differentiator between one product and another, and a sign to identify the origin of goods and services. Not infrequently there are parties who have bad intentions to find shortcuts to success by piggybacking on the reputation (passing 0ff) of a well-known brand. Even though this has been regulated in Indonesia, it cannot be separated from the problem of infringement of trademark rights which has led to disputes in court, one of which is a trademark dispute between STARBUCKS CORPORATION and PT. SUMATERA TOBACCO TRADING COMPANY. The purpose of this study is to find out the regulation of trademarks and geographical indications governing well-known brands, how is the legal protection of well-known brands when there are registrations of other brands which have divisions into different classes, and how is the legal protection of the Starbuck brand, which has similarities in principle to the Starbuck brand registered in a different class, case study of District Court decision No: 51/Pdt.Sus/Merek/2021/PN Niaga Jkt.Pst Juncto Supreme Court decision No: 836K/Pdt.Sus-HKI/2022. The approach used is a normative juridical approach, and is descriptive in nature with secondary data sources which include primary, secondary and tertiary legal materials. The technique used in library research uses qualitative methods. The results of the study found that the lawsuit between the Plaintiff's Starbucks brand and the Defendant's Starbucks brand had similarities in principle. The researcher is of the opinion that the panel of judges is right in giving their legal considerations, namely there are similarities, similarities in the form of arrangement and number of letters, as well as the similarity in sound and assessment of the Plaintiff's Starbucks brand with the Defendant's Starbucks brand.